Des femmes qui voyagent - Denise Brahimi (Multilinguales)
This paper is dedicated to three women of the 19th century, Flora Tristan, George Sand and Isabelle Eberhardt. None of them chose travelling as her main occupation, Flora Tristan had to go abroad because of some special circonstances in her life, George Sand wanted to consider the main role of travel in a woman’s life, Isabelle Eberhardt was unable to stay quietly among the ladies of colonial Algeria. Being at the same time writers, they had the desire and the capacity to transmit their experience of travelling.Thanks to them, we understand that through travelling, women of the 19th century found a way to free and assert themselves.